2001
DOI: 10.1067/mva.2001.118805
|View full text |Cite
|
Sign up to set email alerts
|

Is bilateral ultrasound scanning of the legs necessary for patients with unilateral symptoms of deep vein thrombosis?

Abstract: Routine bilateral lower-extremity venous duplex studies are not necessary in outpatients presenting with unilateral symptoms. In many outpatients, a single-limb study will suffice. If a patient is found to have a DVT on the symptomatic side, then we believe that a bilateral study is indicated. We do believe that routine bilateral scanning of inpatients remains justified. This algorithm may save technician time and increase vascular laboratory efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
2
14
1
1
Order By: Relevance
“…Outpatients generally are healthier and are less likely to have other comorbidities that may increase the risk of thrombosis in the asymptomatic limb. Garcia et al 9 reported that 5% of their 250 inpatients in their study had DVT in only the asymptomatic leg. None of their 276 outpatients had thrombus confined to the asymptomatic leg.…”
Section: Discussionmentioning
confidence: 97%
“…Outpatients generally are healthier and are less likely to have other comorbidities that may increase the risk of thrombosis in the asymptomatic limb. Garcia et al 9 reported that 5% of their 250 inpatients in their study had DVT in only the asymptomatic leg. None of their 276 outpatients had thrombus confined to the asymptomatic leg.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 According to various authors, the percentage of detected distal DVT ranges from 5 to 76.5%. 23,24 DVT pharmacological prophylaxis with LMWH decreases its rate of what has been reported through multiple studies. 5,14,25,26 Most of the authors recommend the aforementioned level of prophylaxis until the end of the 2nd 1,25 or 3rd month post-injury.…”
Section: 3710mentioning
confidence: 99%
“…Likewise, although contrast venography is considered the criterion standard for DVT, VDUS has become the ''standard of care.'' [4][5][6]13,14 Second, a study of consecutive patients would have eliminated possible selection bias, although the two previous prospective studies were also limited by convenience samples. It may be that those patients whom an EP-sonographer feels comfortable examining with US can be adequately assessed.…”
Section: Limitationsmentioning
confidence: 99%
“…Contrast venography is the criterion standard for diagnosing DVT, but it is invasive and has been replaced by venous duplex ultrasonography (VDUS) as the initial diagnostic test. [4][5][6] Recently, some centers have begun using computed tomography (CT) venography, with comparable results. [7][8][9] Although most emergency departments (EDs) are able to obtain VDUS during business hours, this often requires patients' being gone from the ED for several hours.…”
mentioning
confidence: 99%